An Overmodulation Algorithm Based on Svm for Power Quality Applications - Rojas-Lobos, F; Diaz-Diaz, M; Droguett-Olea, G; Uriarte-Gonzalez, M (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper proposes a new overmodulation algorithm based on SVM in which the overmodulation region is avoided to reduce harmonic distortion and do not incorporate additional unexpected harmonics. Thereby, when the reference signal exceeds the modulation zone, then the algorithm reduces the fundamental signal component and maintains the magnitude of the reference harmonic components, preventing the reference signal scape from the modulation limits. The algorithm is validated by the simulation of a three-phase voltage source converter operating as a shunt active filter in a three-wire network with a highly inductive and non-linear load. © 2018 IEEE.